ACCESS TO JUSTICE: IN CONSIDERING LOSSES OF GIVING THE RIGHT OF EXPLOITATION (STUDIES IN MESUJI LAMPUNG) - Winanti, Atik; Nugroho, Andriyanto Adhi; Wahyuningsih, Yuliana Yuli (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2019)
Conflict in Mesuji can indeed be categorized as a chronic agrarian conflict. This chronic condition can?t be separated from the complex dynamics of conflict, involving various parties with different interests. Case of indemnification Barat Selatan Makmur Investindo Company with the community in Mesuji is also at the same time a fact that shows that forests do not merely present ecological facts, but a landscape that is socially constructed to fulfill some functions, namely as a region of life, a place to grow the collective identity of a community group, developing the culture of society